A Synopsis of Parkinson's Disease - Qayyum Rana, Abdul (IntechOpen, 2014)
Parkinsons disease is a disabling neurological condition with both motor and non-motor symptoms for which no cure is available at this stage. This book is unique in covering the most important topics related to Parkinsons disease. Current research and updates about some non-motor symptoms, as well as surgical treatment of Parkinsons disease, in addition to the long term complications of pharmacological treatments have been presented. This book can be used by physicians, researchers and neuroscientists who want to learn new information about these topics related to Parkinsons disease. Authors of the individual chapters are well known in their fields and the book has been edited by a world renowned Parkinsons disease expert.